2022
DOI: 10.3389/fimmu.2022.883560
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytokines in Thymic Regulatory T Cell Generation: Overview and Updates

Abstract: CD4+CD25+Foxp3+ Regulatory (Treg) T cells are mainly generated within the thymus. However, the mechanism of thymic Treg cell (tTreg cell) generation remains to be fully revealed. Although the functions of TCR/CD28 co-stimulation have been widely accepted, the functions of cytokines in the generation of tTreg cells remain highly controversial. In this review, we summarize the existing studies on cytokine regulation of tTreg cell generation. By integrating the key findings of cytokines in tTreg cell generation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 98 publications
0
6
0
Order By: Relevance
“…The thymus serves as a crucial immunological organ wherein T cells undergo development and maturation. Its stromal cells, including thymic epithelial cells, are capable of producing various cytokines, including IL-2, IL-4, and TNF-α, that contribute to the regulation of cell-mediated immunity ( 32 ). Structurally, the thymus is composed of two regions: the cortex and medulla.…”
Section: Discussionmentioning
confidence: 99%
“…The thymus serves as a crucial immunological organ wherein T cells undergo development and maturation. Its stromal cells, including thymic epithelial cells, are capable of producing various cytokines, including IL-2, IL-4, and TNF-α, that contribute to the regulation of cell-mediated immunity ( 32 ). Structurally, the thymus is composed of two regions: the cortex and medulla.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why MCs regain their capacity to degranulate ex vivo or after birth in vivo due to a reduction in fetal Treg, leading to allergic reactions. Hence, it will be important to conduct future studies start focusing on the crosstalk between MC and other immune subsets during the fetal stage and after birth 19,67‐69 …”
Section: Role Of Fmc In the Fetal‐maternal Immune Responses During In...mentioning
confidence: 99%
“…Hence, it will be important to conduct future studies start focusing on the crosstalk between MC and other immune subsets during the fetal stage and after birth. 19,[67][68][69] Recently, it was reported that Omalizumab can transfer allergen to the fetus via a complex with IgE/allergen and transport via the FcRn, 62,70 opening the door to evaluate the possible transmission of other promising AIT 16 through MFI and the impact the AIT transmission on the modulation and the sensitivity of the fetal and neonatal immune subsets including fMC.…”
Section: Role Of Fm C In the Fe Tal-maternal Immune Re S P Ons E S Du...mentioning
confidence: 99%
“…IL-2-CD25 signaling pathway deficiency causes severe inflammation in the oral mucosa IL-2 is a vital cytokine for Treg cell development, and the loss of IL-2 causes the deficiency of mature Treg cells (20)(21)(22). To further confirm the function of Treg cells in the oral mucosa, we bred Il2 -/mice to investigate inflammation development of oral mucosa in these mice.…”
Section: Treg Cell Deficiency Causes Severe Inflammation In Oral Mucosamentioning
confidence: 99%
“…Manipulating Treg cells has been shown to be a promising strategy to suppress and treat autoimmune and inflammatory diseases, including inflammatory bowel disease (IBD), experimental autoimmune encephalomyelitis (EAE), Type I diabetes (T1D), asthma, and arthritis (17)(18)(19). The IL-2-CD25 signaling pathway has been determined to be dramatically important for Treg cell generation in the thymus and periphery, as the absence of IL-2-CD25 signaling pathway cause Treg cell deficiency and severe systemic inflammation (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%